Kinetics of Immunoglobulins in Septic Shock Patients Treated With an IgM- and IgA-Enriched Intravenous Preparation: An Observational Study - Berlot, Giorgio; Scamperle, Alice; Istrati, Tatiana; Dattola, Roberto; Longo, Irene; Chillemi, Antonino; Baronio, Silvia; Quarantotto, Giada; Zanchi, Silvia; Roman-Pognuz, Erik; Bixio, Mattia; Tomasini, Ariella (Frontiers in Medicine, 2021)
Objective: To assess the variations of the blood levels of immunoglobulins (Ig) in septic shock patients treated with an Ig preparation enriched in IgM and IgA (eIg). Design: The blood levels of Ig in survivors (S) and non-survivors (NS) of a group of septic shock patients were measured before the initial administration (D0) and 1 (D1), 4 (D4), and 7 (D7) days thereafter. The SAPS II score, the capillary permeability, the primary site of infection, the antibiotic appropriateness, and the outcome at 28 days were also assessed. Results: In the interval D0–D7, the IgM increased significantly only in the S while remained stable in NS; the IgA significantly increased in both groups; the IgG did not vary significantly in both groups. At D4, the capillary permeability significantly decreased in S but not in NS. Conclusions: The kinetics of the different classes of Ig after eIg were different between S and NS. This could be related either to (a) different capillary permeability in the two groups or to (b) higher Ig consumption in NS. Further studies to confirm the benefits of eIg in the treatment of sepsis syndrome and to define the specific target population and the correct eIg dose are warranted.